Penggunaan Media Audio Visual untuk Meningkatkan Kemampuan Penglihatan dan Pendengaran Anak di TK Yazida NW Tangar Lombok - Suhaini, Suhaini (AS-SABIQUN, 2026)
This study was motivated by the development of digital technology that affects the learning process of early childhood and encourages the use of more up-to-date media, including audio-visual media. This study aims to discuss the impact of the use of audio-visual media on the visual and auditory abilities of early childhood. This study used a qualitative method, with data collection techniques through interviews, observation, and documentation conducted at Taman Kanak-Kanak Yazida NW Tangar Lombok. The results showed that the implementation of audio-visual media in training the visual and auditory abilities of early childhood was carried out through various forms, such as educational videos, children’s songs, learning animations, and illustrated stories with sound. The media were used in a structured manner in daily learning activities, especially in listening activities and in introducing basic concepts, such as colors, shapes, numbers, and animals. Teachers played an active role in directing and providing further stimulation after the children watched or listened to the media. The children’s responses and involvement in the use of audio-visual media showed positive results, as indicated by enthusiasm, focus, and active involvement in learning activities. The children also appeared more interested in listening and showed expressions of joy when the media were used. This study concludes that the use of audio-visual media has a positive impact on the development of the visual and auditory abilities of early childhood and supports the creation of more engaging and participatory learning.